Strategi Pemasaran untuk Meningkatkan Keunggulan Bersaing di Era Digital pada UMKM Donat Ratu - Anissa Rahmawati (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Currently, business development in Indonesia is increasing in complexity, competition, change and business uncertainty. This situation creates intense competition between entrepreneurs. Competition in the culinary business is one of the fields that has more and more enthusiasts and makes competition in the culinary business increase. Donat Ratu MSME is an MSME established in 2019 in Kalisat District that uses social media as a place to market its products. This research was conducted to solve existing problems at Donat Ratu MSMEs, namely alternative marketing strategies to increase competitiveness in the digital era with SWOT analysis. The SWOT model used in this research is the strategy-formulation analytical framework, which is divided into 3 main stages, namely the input stage, the matching stage, and the decision stage. This research uses descriptive qualitative research methods. The data and information collection methods used in this research were obtained directly through interviews and observations, and indirectly through literature studies. The results of this study are based on SWOT analysis, the position of MSME Donat Ratu is in a favorable position so that the suitable strategy to use is an intensive-aggressive strategy and horizontal integration. The strategy that can be carried out by UMKM Donat Ratu is to develop products and expand market segments. Keywords: Digital Era, IE Matrix, Marketing Strategy, SWOT Analysis, SWOT Matrix